Forecasting future irrigation water sustainability in upper Bernam river basin Malaysia - Alansi, Abdul Wahab; Mohd Som, Mohd Amin; Ahmad Dahlan, Abdul Rahman; Abdul Rahman, Irdawati; Hasan, Saliza (2009)
The Bernam river basin where Proton city is located is rapidly developing, changing from agriculture based to an industrial area. Land development can be associated with increased impervious areas causing increase in surface runoff and decrease in ground water recharge. The study area is the main source of irrigation water supply for paddy fields in the downstream of the watershed. The required water for paddy irrigation should be made available continuously for double cropping via maintaining high base flows so that enough water is available for irrigation during the dry season. Soil and Water Assessment Tool (SWAT) model was used to study the effects of land-use changes on water resources sustainability. The study results confirmed that change of land-use pattern altered the runoff volume. In the year 2020 runoff is predicted to increase in the rainy season due to large increase of land use changes especially urban and forest, which then accelerate runoff and decrease base flow due to an increase in the impervious area. Providing such information in AgriGRID will help planners and decision makers to take the effect of land-use changes into account when formulating future plans for land development and include some structural best management practices (BMPs) within their future plan to control and manage water resources in the watershed.